Relevansi Zakat dengan Sustainable Development Goals (SDGs): Perspektif Maqasid al-Shari'ah - Mazroatus Saadah; Uswatun Hasanah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2021)
This study aims to explain the common goals of zakat and Sustainable Development Goals (SDGs) from the perspective of maqasid al-Sharia. Zakat programs developed by the National Board of Amil Zakat (BAZNAS), especially in the economic, social and humanity, health, and education fields are in line with the SDGs programs launched by the United Nations, especially the programs number 1-4 namely no poverty, zero hunger, good health and well-being, and quality education. By using the maqasid al-Sharia approach, the SDGs programs that are included in the level of urgent needs (daruriyyah) and in accordance with the purpose of zakat, take precedence in its implementation such as the Mustahik Economic Empowerment Institute established by BAZNAS to improve the quality of life of mustahik. (Penelitian ini bertujuan untuk menjelaskan tujuan umum zakat dan SDGs dari perspektif maqasid al-Sharia. Program-program Zakat yang dikembangkan oleh Badan Amil Zakat Nasional (BAZNAS) khususnya dalam bidang ekonomi, sosial kemanusiaan, kesehatan, dan pendidikan sejalan dengan program-program tujuan pembangunan berkelanjutan (SDGs) yang dicanangkan oleh PBB, khusunya program no poverty, zero hunger, good health and weel-being, and quality education. Dengan menggunakan pendekatan maqasid al-Sharia, maka program-program SDGs yang masuk dalam tingkat kebutuhan yang mendesak (daruriyyah) dan sesuai dengan tujuan zakat, diutamakan dalam pengimplementasiannya seperti Lembaga Pemberdayaan Ekonomi Mustahik yang didirikan BAZNAS dengan tujuan untuk meningkatkan kualitas hidup mustahik.)